Соціальний потенціал розвитку промисловості України: методологічні аспекти, чинники активізації - Новікова, О.Ф.; Логачова, Л.М. (Економіка промисловості, 2017)
Досліджено концептуальні підходи до визначення змісту та структури соціального потенціалу за рівнями, видами та завданнями формування. На основі узагальнення визначено та охарактеризовано складові соціального потенціалу промисловості, подано авторське тлумачення цього поняття. Проаналізовано показники діяльності суб’єктів господарювання у промисловості Україні, розглянуто сучасні тенденції використання трудового потенціалу промислових підприємств. Розроблено пропозиції та рекомендації щодо шляхів активізації соціального і трудового потенціалу промисловості в контексті економічної ефективності та соціальної справедливості. Исследованы концептуальные подходы к определению содержания и структуры социального потенциала по уровням, видам и задачам формирования. На основе обобщения определены и охарактеризованы составляющие социального потенциала промышленности, представлено авторское толкование этого понятия. Проанализированы показатели деятельности субъектов хозяйствования в промышленности Украины, показан высокий удельный вес промышленности в общем объеме реализации продукции (товаров, услуг) и численности занятых. Рассмотрены современные тенденции использования трудового потенциала промышленных предприятий. The conceptual approaches to determining the content and structure of social potential by levels, types and tasks of formation are explored. On the basis of generalization, the components of the social potential of industry are defined and characterized, the authors’ interpretation of this concept is presented.The authors’ interpretation presents an understanding of the social potential of industry as a systemic set of organizational and managerial, individual-personal factors, incentives and motives, factors of production and resources, that are realized in the process of joint activity with the aim of ensuring economic growth. The social potential of an industrial enterprise as a systemic component of the social potential of industry is characterized by a combination of social factors, manifested through the interaction of the social and labor potential and the social infrastructure of the enterprise.The indicators of the economic entities’ activity in the industry of Ukraine are analized, a high specific weight of industry in the total volume of sales of products (goods, services) and the number of employees is shown. Modern trends in the use of labor potential of industrial enterprises are considered.The offers and recommendations on the formation of a set of social and personnel policies aimed at developing the educational and professional level of personnel, the system of continuous retraining refinment and improving the skills of personnel, advancing the technologies for professional training of personnel and mechanisms for financing the costs of training and retraining of personnel are made.